The reality of administrative and technical empowerment of the coaching staff in basketball sports clubs - hussein, ali (Journal of Physical Education, 2023)
The importance of research lies in the results of this research and its importance in developing the performance of coaches if committed, which in turn will lead to higher overall performance in the Iraqi Basketball League the research aims to identify the reality of empowerment among the coaches of the Iraqi Basketball Federation and employees of the Iraqi clubs, The research sample consisted of Iraqi Basketball Federation coaches and staff at Baghdad Clubs who were commissioned in the years (2018, 2019, 2020, 2021) Training basketball teams in Iraq clubs, and their number was (110). The research tool for gathering information was a questionnaire that the researcher built, subjected to scientific requirements, and presented to the experts until it became final. The researcher reached several conclusions, the most important of which is that the management used by the clubs is bureaucratic management that believes in confining authority to senior management and that all areas of empowerment (Information, power participation, development, and training) need to be strengthened, and one of the most important recommendations recommended by the researcher is to establish clear criteria and information for everyone on everything about choosing (assistants, players, camps, training halls, fixtures, tournaments, friendly matches) and other logistics.